اكتشاف وتشخيص أعطال نظام خلايا كهروضوئي - حداد, إبراهيم; حجار, عمار; صبيح, مسعود (Latakia University Journal -Engineering Sciences Series, 2019)
In recent years, solar energy has been received a great attention because it is free, clean and sustainable for electrical energy production. Where, the use of the photovoltaic (PV) systems has been increased widely due to the reduction in the prices of the PV panels due to the technology advancement in this field. However, the photovoltaic systems need continuous monitoring and periodic maintenance in order to get their optimal investment. The photovoltaic systems are prone to many faults, at different levels, starting from the failure of some cells to outage the whole panel(s) from a service and this may be developed to threaten the entire photovoltaic strings or arrays, thus it may results in reduction in their efficiency and fires occurring. To minimize the serious consequences of these faults, it is important to study the behavior of the PV systems and diagnose them as quickly as possible to ensure their reliability. Therefore, In this paper, a method based on monitoring the change in power value and voltage deviation was presented in the photovoltaic cells array with the total cross-tide (TCT) method for detecting and diagnosing the prominent photovoltaic array faults (open-circuit fault, short-circuit fault, shading condition) in real-time. To test the performance of this method in detecting and diagnosing faults in the photovoltaic cells array with the total cross-tide (TCT) method, in this paper has been modeling this array and simulating the prominent faults on it, using MATLAB / SIMULINK / SIMSCAPE environment. Modeling and simulation results have proven the efficiency of this method in detecting and diagnosing faults in the photovoltaic cells array with the total cross-tide (TCT) method, accurately and efficiently in real time. حظيت الطاقة الشمسية خلال السنوات الأخيرة باهتمام كبير كونها طاقة مجانية نظيفة ومُستدامة لإنتاج الطاقة الكهربائية. حيث ازداد استخدام أنظمة الخلايا الكهروضوئية بشكل واسع بسبب انخفاض أسعار الألواح الكهروضوئية نتيجة للتقدم التكنولوجي في هذا المجال. لكن، تحتاج أنظمة الخلايا الكهروضوئية هذه إلى المُراقبة المُستمرة والصيانة الدورية بهدف الاستثمار الأمثل لها. تتعرض أنظمة الخلايا الكهروضوئية إلى العديد من الأعطال، على مستويات مُختلفة، بدءاً من تعطل بعض الخلايا الكهروضوئية إلى خروج ألواح كاملة عن الخدمة، وقد يتطور الأمر ليُهدد سلاسل أو صفوف كهروضوئية بأكملها مما يُؤدي إلى الحد من كفاءتها وإلى حدوث حرائق. للحد من النتائج الخطيرة المُترتبة عن حدوث تلك الأعطال، من الأهمية بمكان دراسة سلوك أنظمة الخلايا الكهروضوئية لتشخيص أعطالها بأسرع وقت مُمكن وذلك لضمان عملها بموثوقية عالية. لذا، تم في هذا البحث تقديم طريقة تعتمد على مُراقبة التغير في قيمة الاستطاعة وانحراف الجهد في مصفوفة الخلايا الكهروضوئية، ذات التشكيل بطريقة التقاطع الكلي/المُتكامل (TCT)، لأجل اكتشاف وتشخيص أبرز الأعطال فيها (عطل الدارة المفتوحة، عطل الدارة القصيرة، حالة التظليل) في الزمن الحقيقي. لاختبار أداء هذه الطريقة في اكتشاف وتشخيص الأعطال في مصفوفة الخلايا الكهروضوئية ذات التشكيل بطريقة التقاطع الكلي/المُتكامل (TCT)، تم في هذا البحث نمذجة هذه المصفوفة وتم مُحاكاة أبرز الأعطال عليها، وذلك باستخدام بيئة MATLAB/SIMULINK/SIMSCAPE. لقد أثبتت نتائج النمذجة والمُحاكاة كفاءة هذه الطريقة في اكتشاف وتشخيص الأعطال في مصفوفة الخلايا الكهروضوئية، ذات التشكيل بطريقة التقاطع الكلي/المُتكامل، بدقة وكفاءة عاليتين في الزمن الحقيقي.